Financial Performance Analysis of Village Fund Allocation Management Based on Financial Ratios at Simanaere Village Office, Gunungsitoli Idanoi District, Gunungsitoli City - Waruwu, Putri Destari; Telaumbanua, Aferiaman; Waruwu, Sukaaro; Harefa, Idarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to analyze the financial performance of Village Fund Allocation (ADD) in Simanaere Village, Idanoi District, Gunungsitoli City, based on the calculation of financial ratios, namely effectiveness ratio and growth ratio. The analysis method used in this research is descriptive with both quantitative and qualitative approaches. The researcher obtained secondary data in the form of the realization report of the Village Revenue and Expenditure Budget (APBDes) of Simanaere Village from 2019 to 2021, and primary data in the form of interview results with the government of Simanaere Village. Data collection techniques used were interviews and documentation. The results of this research indicate that the financial performance of ADD management in Simanaere Village from 2019 to 2021 is categorized as effective, with an average effectiveness rate of 99.41%. However, the growth rate is categorized as negative, with an average of -5.9%.